Location selection criteria for field hospitals: A systematic review - Keyvan Fardi; Ghader Ghanizadeh; Mohammadkarim Bahadori; Samaneh Chaharbaghi; Sayyed Morteza Hosseini Shokouh (Health Promotion Perspectives, 2022)
Background: Establishing field hospitals is a critical task for governments to complete following disasters, with the first step being to identify suitable locations. Although field hospitals are similar to permanent hospitals and temporary shelters, no research in English has been conducted to extract the location selection criteria for field hospitals from those for hospitals and temporary shelters. Methods: A meta-synthetic approach was used to review all related qualitative, quantitative, and mixed studies published in English between January 2010 and June 2020 to identify new field hospital site selection criteria distinct from those used to select a permanent hospital and temporary sheltering sites. Results: From 4317 screened records, 24 articles were eventually identified as eligible studies, through which 151 open codes, 21 axial codes, and nine themes were identified. The top three axes included proximity to main roads, proximity/distance to permanent hospitals, and proximity/distance to other medical centers. Conclusion: By considering a field hospital as a facility with certain characteristics similar to permanent hospitals and temporary shelters, it is possible to identify specific new criteria and sub-criteria by extracting items common to permanent hospitals and temporary shelter site selection studies.